Six new, unusually small ants of the genus Leptomyrmex (Hymenoptera: Formicidae) - Smith, Derek J.; Shattuck, Steve (Zootaxa, 2009)
The ant genus Leptomyrmex contains 41 named taxa which are limited to eastern Australia, New Guinea and New Caledonia. While most species are large and distinctive, a few species are much smaller and have only recently been recognised as belonging to this genus. These six species, informally called micro-Leptomyrmex, are restricted to rainforests and wet sclerophyll forests in two relatively small regions of eastern Australia. All are described here for the first time and include L. aitchisoni n. sp., L. burwelli n. sp., L. dolichoscapus n. sp., L. garretti n. sp., L. pilosus n. sp. and L. ramorniensis n. sp.